A meta analytic approach to testing for panel cointegration - Christoph Hanck (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2007)
We propose new tests for panel cointegration by extending the panel unit root of Choi [2001] and Maddala and Wu [1999] to the panel cointegration case. The tests are flexible, intuitively appealing and relatively easy to compute. We investigate the finite sample behavior in a simulation study. Several variants of the tests compare favorably in terms of both size and power with other widely used panel cointegration tests.
Keywords: 519; panel cointegration tests; Monte Carlo study; meta analysis; Panel; Kointegration; Meta-Analyse; Theorie